Предмет: Алгебра,
автор: Аноним
ПОМОГИТЕ ПОЖАЛУЙСТА ОЧЕНЬ СРОЧНО!!!
Упростите выражение:
1) (a+1)(a²-a+1)-a³
2) (x+y)(x²-xy+y²)-x(x²+y²)
3) (m-2)(m²+2m+4)+8
4) (c+3)(c²-3c+9)-27
Ответы
Автор ответа:
0
(a+1)(a²-a+1)-a³=a^3+1^3-a^3=1
(x+y)(x²-xy+y²)-x(x²+y²)=x^3+y^3-x^3-xy^2=y^2(y-x)
(m-2)(m²+2m+4)+8=m^3-2^3+8=m^3-8+8=m^3
(c+3)(c²-3c+9)-27=c^3+3^3-27=c^3+27-27=c^3
(x+y)(x²-xy+y²)-x(x²+y²)=x^3+y^3-x^3-xy^2=y^2(y-x)
(m-2)(m²+2m+4)+8=m^3-2^3+8=m^3-8+8=m^3
(c+3)(c²-3c+9)-27=c^3+3^3-27=c^3+27-27=c^3
Похожие вопросы
Предмет: Математика,
автор: samarinaulia58
Предмет: Алгебра,
автор: Аноним
Предмет: Алгебра,
автор: smart9073
Предмет: Математика,
автор: Ket123456789
Предмет: Алгебра,
автор: Мамбо